Parent versus child report of young children's parasocial relationships in the United States. Issue 4 (1st October 2016) - Richards, Melissa N.; Calvert, Sandra L.
Abstract: This study examines parent perceptions of their young children's one-sided, emotionally tinged relationships with media characters, also known as parasocial relationships (PSR). Prior research has collected data on young children's PSR by surveying parents, while other studies have relied directly on child interview. The current study is the first to compare children's answers to those of their parents. Factor analyses revealed that parents and children both reported three components of children's PSR: social realism, attachment and character personification (parents) or attachment and friendship (for their children), and humanlike needs . Both parent and child reports accounted for approximately 60% of the variance in children's PSR. Nonetheless, only approximately one-third of parents and children reported on the same favorite character. The implications for research on children's PSR using both parent and child reports are discussed.